Research Progress of Two-way Social Support for the Elderly - Huang, Suli (International Journal of Social Sciences and Public Administration, 2024)
This paper gives a comprehensive overview of the classification of social support, as well as the definition of two-way social support, its intrinsic meaning and corresponding measurement tools. At the same time, through a detailed review of the international and Chinese two-way social support research status, the current research hotspots and trends are explained. In particular, this paper points out the shortcomings of the research on two-way social support for the elderly in China. In view of these shortcomings, this paper proposes future research directions and development prospects in this field, in order to provide valuable references for further research and practice in this field.